The Need for Open Science - Abd Rahman, Noorsaadah (Journal of Research Management and Governance, 2019)
Open Science is about sharing knowledge where research data and other research processes are freely available, under terms that enable reuse, redistribution and reproduction of the research and its underlying data and methods. The availability of these data publicly should promote the translation of research output into innovation and new technologies. In addition, making research data and knowledge publicly available to others would help to build trust on the research findings and could support public policies and further investments.